2004
DOI: 10.1038/sj.cgt.7700686
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, in vivo, evaluation of antiangiogenic and antineoplastic gene products by nonviral transfection of tumor cells

Abstract: Using a nonviral, electroporation-based gene transfection approach, we demonstrate the efficient and consistent transfection of two poorly immunogenic tumor cell lines: B16F10 melanoma and renal carcinoma (RENCA). Three genes, IL-12, angiostatin (AS), and an endostatin:angiostatin fusion protein (ES:AS) were subcloned into a DNA plasmid containing EBNA1-OriP, which was then transfected into B16F10 and RENCA cells. Significant levels of protein were secreted into the culture supernatants of transfected cells in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…To determine whether these results could be reproduced in another murine system, we repeated the experiment using RENCA cells, derived from a murine renal cell carcinoma that is also minimally to moderately immunogenic (16). Results obtained with this model were very similar to those observed with CT26.…”
Section: Treatment Of Renca Tumors In Micementioning
confidence: 55%
“…To determine whether these results could be reproduced in another murine system, we repeated the experiment using RENCA cells, derived from a murine renal cell carcinoma that is also minimally to moderately immunogenic (16). Results obtained with this model were very similar to those observed with CT26.…”
Section: Treatment Of Renca Tumors In Micementioning
confidence: 55%
“…It does not require viral vector construction or virus preparation. Many reports describe electroporation as a technique for promoting electrochemotherapy through the uptake of MTX into cancer cells (17)(18)(19). We also showed that electrochemotherapy was effective in digital chondrosarcoma (20).…”
Section: Discussionmentioning
confidence: 64%
“…Weiss and co-workers used a non-viral, electroporation-based gene transfection approach and obtained efficient and consistent IL-12 transfection of two poorly immunogenic B16-F10 melanoma and renal carcinoma cell lines. Transfected tumor cells were then injected subcutaneously into mice and IL-12 was capable of significantly delaying and reducing the formation of tumors (Weiss et al, 2004).…”
Section: From Ex Vivo Transduced Cells To In Vivo Gene Transfer: Inpumentioning
confidence: 99%